2008
DOI: 10.1161/circulationaha.107.760488
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Control of Adaptive Cardiac Hypertrophy by Acetyltransferase p300

Abstract: Background— Acetyltransferase p300 is essential for cardiac development and is thought to be involved in cardiac myocyte growth through MEF2- and GATA4-dependent transcription. However, the importance of p300 in the modulation of cardiac growth in vivo is unknown. Methods and Results— Pressure overload induced by transverse aortic coarctation, postnatal physiological growth, and human heart failure were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
123
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(132 citation statements)
references
References 55 publications
7
123
2
Order By: Relevance
“…Previous studies have implicated p300 acetyltransferase as a positive regulator of pathologic cardiomyocyte hypertrophy, possibly via its ability to acetylate prohypertrophic transcription factors, such as GATA4, MEF2, and p53 (21,(47)(48)(49)(50). Prior work from our group has shown that Klf15 expression is dramatically reduced during pathologic cardiac hypertrophy, an event that releases repression of GATA4, MEF2, and the p300-p53 transcriptional module (20,21).…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have implicated p300 acetyltransferase as a positive regulator of pathologic cardiomyocyte hypertrophy, possibly via its ability to acetylate prohypertrophic transcription factors, such as GATA4, MEF2, and p53 (21,(47)(48)(49)(50). Prior work from our group has shown that Klf15 expression is dramatically reduced during pathologic cardiac hypertrophy, an event that releases repression of GATA4, MEF2, and the p300-p53 transcriptional module (20,21).…”
Section: Discussionmentioning
confidence: 87%
“…It is known that p300 has multiple functions in different conditions: for example, in the heart p300 activation can lead to heart hypertrophy mediated by myocyte enhancer factor-2 (MEF2) (48), whereas in the brain p300 affects memory function via cAMP response element-binding (CREB) (49). Roles for stressors in these conditions are appreciated, but further molecular mechanisms remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…We found elevated p300 protein levels in mdx heart tissues. High p300 levels are found in the failing heart in humans and mice (4), and combination studies using cardiac p300 transgenic mice and p300 heterozygous knock-out mice showed that mortality and cardiac mass are directly regulated by myocardial p300 protein levels (4). Because a 1.5-3.7-fold overexpression of p300 causes prominent cardiac hypertrophy in p300-transgenic mice (4), the 2.8-fold increase in p300 protein level in the mdx heart is sufficient to induce cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Although p300 is essential for cardiac development (3), it also plays a key role in cardiac hypertrophy and heart failure by acetylating and activating myocyte enhancer factor-2 (4) and GATA4 (5) transcription factors. The dose of p300 seems to be critical for development of cardiac hypertrophy, because overexpression of p300 induces cardiomyocyte hypertrophy in vitro and in vivo, whereas down-regulating p300 ameliorated cardiomyopathy (4). In addition, cardiac fibrosis impairs myocardial diastolic function in hypertrophied and failing hearts, and p300 promotes tissue fibrosis by binding to and activating Smad3 (6).…”
mentioning
confidence: 99%